PENGARUH KOREAN WAVE, BRAND AMBASSADOR, CITRA MEREK DAN ONLINE CUSTOMER REVIEW TERHADAP KEPUTUSAN PEMBELIAN PADA MARKETPLACE SHOPEE WILAYAH KOTA BENGKULU - Putry, Yonda Ahmeiza; Onsardi, Onsardi (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2026)
This study aims to analyze the influence of Korea wave, Brand Ambassador, Brand Image, and Online Customer Review on Purchase Decisions among Shopee marketplace consumers in Bengkulu City. The research method used is quantitative with a multiple linear regression approach. Data were collected through questionnaires distributed to respondents who are active Shopee users in Bengkulu City.  The results indicate that there is a positive and significant influence of Korea wave on Purchase Decisions, meaning that the stronger the influence of Korea wave, the higher the consumer's buying interest. Additionally, Brand Ambassador also has a positive impact on Purchase Decisions, indicating that the stronger the role of the Brand Ambassador, the higher the consumer's purchase decision. However, Brand Image does not have an influence on Purchase Decisions, despite marketing theories often associating brand image with customer loyalty. Meanwhile, Online Customer Review has been proven to have a positive impact on Purchase Decisions, showing that the more positive reviews, the higher the consumer's tendency to purchase products.  Simultaneously, the variables Korea wave, Brand Ambassador, Brand Image, and Online Customer Review collectively influence Purchase Decisions with a significance value of F at 0.000 < 0.05. The findings of this study can serve as a reference for business practitioners in designing more effective marketing strategies to enhance consumer purchase decisions on the Shopee marketplace. Keywords: Korean wave, Brand Ambassador, Citra Merek, Online Customer Review, purchase decision.